Optimalisasi Produktivitas Olahan Produk Zero Waste Limbah Ikan Patin (Pangasius hypophthalmus) pada Poklahsar Dadhen Mandiri di Kepanjen, Kabupaten Malang: Optimization of Productivity in Utilizing Zero-Waste By-Products of Patin Fish (Pangasius hypophthalmus) at the Poklahsar Dadhen Mandiri, Kepanjen, Malang Regency - Intyas, Candra Adi; Handayani, Wahyu; Swara, Suluh Elman; Adilvy, Rizky Daly (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The Poklahsar Dhaden Mandiri was newly established in February 2025, utilising catfish fillet waste as the primary raw material for producing sempol and tahu bakso. However, the production tools are still manual and limited, making large-scale production challenging. Meanwhile, consumer responses have been very positive, with a significant demand observed during the first two months of operation. Therefore, this Community Partnership Empowerment Program (PKM) aims to optimize productivity by providing appropriate technologies, including a bowl cutter machine and a dough-forming machine. The program's methods include socialization, training, technology implementation, mentoring, and evaluation. The results of the community service activities show an approximately 70% reduction in costs, time, and labour, and a threefold increase in profit compared to the previous condition. The bowl cutter machine helps reduce costs and maintain product hygiene, while the forming machine accelerates the dough moulding process and produces more uniform products.